A REVIEW OF CURRENT BOVINE OBSTETRICAL PRACTICES - GHUMAN, S P S; SINGH, N (The Indian Journal of Animal Reproduction, 2022)
The dairy animal population especially buffalo suffers from various obstetrical problems, the solution for some of these have been devised and are in process for the others. There is need to understand management factors associated with uterine torsion in buffaloes, the physiological and cardiovascular impact of dystocia. This will help in timely resuscitation of dystocia-affected dam through the use of tranquilizers, glucocorticoids plus antioxidants and crystalloid plus colloid based fluid therapy. Huge success has been achieved in cervical massage or intracervical treatment for dilatation of incompletely dilated cervix as well as timely and appropriate handling of an obstetrical case by understanding the importance of time factor. The use of uterine lubricants improves success rate. Fetotomy should be used as preferred obstetrical procedure by making the availability of an appropriate Fetotomy kit and the knowledge of ‘Strength-Stamina-Skill’ for carrying out fetotomy procedures.